2022
DOI: 10.2147/ijgm.s372158
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Risk Prediction Model for Left Ventricular Aneurysm in Patients with Acute Myocardial Infarction in Northwest China

Abstract: Left ventricular aneurysm (LVA) is a severe and common mechanical comorbidity with acute myocardial infarction (AMI) that can present high mortality and serious adverse outcomes. Accordingly, there is a need for early identification and prevention of patients at risk of LVA. The aim of this study was to develop and validate a risk prediction model for LVA among AMI patients in Northwest China. Methods: A total of 509 patients with AMI were retrospectively collected between January 2018 and August 2021. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a subsequent study involving AMI patients who undergo PCI, Masayuki Mor et al [ 34 ] have found that peak CK levels, heart rate, and final TIMI flow grading are all independently linked to the onset of left ventricular apical aneurysms (LVAA). Moreover, Yuanming Xing and team [ 35 ] have proposed a ventricular aneurysm predictive model rooted in seven key parameters: age, cardiovascular disease history, left ventricular ejection fraction, ST-segment elevation, prior PCI experiences, mean platelet volume, and aspartate transaminase levels. Impressively, their model showcases robust predictive efficacy, boasting an AUC of 0.908.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study involving AMI patients who undergo PCI, Masayuki Mor et al [ 34 ] have found that peak CK levels, heart rate, and final TIMI flow grading are all independently linked to the onset of left ventricular apical aneurysms (LVAA). Moreover, Yuanming Xing and team [ 35 ] have proposed a ventricular aneurysm predictive model rooted in seven key parameters: age, cardiovascular disease history, left ventricular ejection fraction, ST-segment elevation, prior PCI experiences, mean platelet volume, and aspartate transaminase levels. Impressively, their model showcases robust predictive efficacy, boasting an AUC of 0.908.…”
Section: Discussionmentioning
confidence: 99%